Using the X-linked inhibitor of apoptosis (XIAP) as a therapeutic agent in rodent models of retinal degeneration - Petrin, Dino P (University of Ottawa (Canada), 2005)
Retinitis Pigmentosa (RP) is the leading cause of hereditary blindness. The clinical manifestations of RP are night blindness, loss of peripheral vision leading to tunnel vision and a decreased electroretinogram (ERG) amplitude. There are numerous genes that when mutated cause RP. Regardless of the causative mutation, the end point is the same, photoreceptor cell death by apoptosis or programmed cell death (PCD). Interestingly, though all photoreceptors in an affected individual would have a mutation, disease progresses at a relatively slow rate indicating the affected cells can function. It is unclear as to why completely unrelated mutations would cause photoreceptors to die via the same mechanism. Somatic gene replacement studies using viral vectors in animal models have been successful in slowing down disease. However, attempting to cure all retinal degeneration mutations by this approach would be costly and difficult for two reasons. First, there are some mutations that comprise a small percentage of all RP cases and the cost/benefit ratio to develop a therapeutic agent for a few people would be enormous. Secondly, a number of genes that cause retinal degenerations have not been cloned. A more practical approach involves preventing apoptosis of the photoreceptor cell. The advantage of this approach is that the causative mutation does not need to be known. Developing a single therapeutic agent to target RP would also be economically more favourable than developing multiple therapeutic agents. The X-linked Inhibitor of Apoptosis (XIAP) can inhibit cell death from numerous triggers both in vitro and in vivo. XIAP prevents apoptosis by binding to and inhibiting caspase-3, -7 and -9. Work presented here shows that adeno-associated virus (AAV) encoding XIAP is neuroprotective when injected sub-retinally in an acute retinal degeneration model in Sprague Dawley rats. In addition, transgenic mice overexpressing XIAP throughout the neural retina have normal retinal morphology and their ERGs appear normal. These findings suggest that XIAP holds promise as a therapeutic agent in the treatment of hereditary retinal diseases such as retinitis pigmentosa.
Keywords: Biology, Cell.; Biology, Microbiology.; Health Sciences, Pathology.